GLOBAL MEDIA INFLUENCE ON MODERN WORLD POLITICAL PROCESSES: A CONSTRUCTIVIST APPROACH - T. I. Tyukaeva (Vestnik MGIMO-Universiteta, 2017)
Global media, its functioning and its influence on world politics is a popular topic of research. Media is traditionally seen among instruments a state uses in its foreign and domestic policies. Liberal pluralists identify global media outlets as relatively independent actors that interact with other states and non-state actors and have the potential to influence global political processes. However, neither of these two main approaches seems to fully answer the question about what shapes the specific nature of modern media in its media-media interaction as well as interaction with other non-state actors and states? And their specific nature taken into consideration, how can modern media impact world politics? This article aims to answer both of these questions. The article analyzes the existing theoretic approaches to studying media and its influence on world politics, identifies the key features of functioning of the modern global information space, observes the main aspects of interaction between the media, on the one hand, and states and non-state actors, on the other, and studies global media’s means of influencing world politics. The constructivist paradigm shapes the theoretical and methodological framework of the study. The author makes a conclusion about ‘dual nature’ of modern media, which may be among means (used by states and non-state actors) of constructing the ‘reality of world politics’ and act as a relatively independent participant of this ‘reality’. Global media outlets are the main actors in global information space, they shape it and define the dynamics of its development, and at the same time they are influenced by the processes unfolding within it. Moreover, the author stresses that the current state of IT development makes the global information space as an integral organism functioning in accordance with its own internal logic. This functioning is based on interaction and interinfluence of various media outlets (of all shapes and levels) that broadcast and exchange competing visions and cultural stereotypes, i.e. ‘social constructs’. The result of this dynamic interaction is a specific – media – reality, which has become one of the key dimensions of modern world political processes.